The context theory in support of interfaith dialogue: the case of the verse (Q 9.5) - Bakour Mohamad, Bachar (2019)
Depending upon the diametrically opposed views of interpreting the sacred text, religion, an increasingly more vital and shaping force in both personal and public life, can either promote global peace or pervasive conflict. Therefore, peace among nations cannot be achieved without peace among religions. The Sword-verse (5) of chapter (9) is assumed to have abrogated numerous verses advocating peaceful coexistence and religious freedom. Accordingly, Muslim extremist discourse takes this verse as basic foundation in dealing with peoples of other faiths. Since awareness of the context is of prime importance, this paper explores how the verse is understood through an analysis of its historical circumstance and linguistic setting and seen in relationship to other verses of religious freedom and dialogue. The paper concludes that the above verse, when appropriately read within its circumstantial boundaries, never condones coercive conversion or endorses militancy.